TET2 modulates proliferation and migration of vascular smooth muscle cells via LEMD2/NOX1/NOX4 signaling pathway. (14th October 2021) - Xie, Y L; Qin, Y C; Li, A H; Yan, Z Q; Qiao, Z D; ,
Abstract: Background: Ten-eleven translocation 2 (TET2), a widely reported DNA hydroxymethylation enzyme, is involved in active DNA demethylation. TET2 may play an critical role in numerous cellular processes by regulating the level of DNA hydroxymethylation and altering gene expression. TET2 expression was proved to be down-regulated in aorta of spontaneously hypertensive rats (SHR) compared to Wistar-Kyoto rats (WKY) as well as in VSMCs subjected to15% cyclic stretch compared to 5% cyclic stretch. However, whether TET2 regulates vascular smooth muscle cells (VSMCs) proliferation and migration and its underlying mechanisms remains unclear. Purpose: The present study aims to investigate whether TET2 affects VSMC proliferation and migration and its possible underlying mechanisms. Methods: TET2 knockdown rat VSMC was established using crispr/Cas9 method. Different expression genes were identified by next generation sequencing (NGS) between TET2 knockdown VSMC and control VSMCs while differentially hydroxymethylated promoter region were identified by hydroxymethylcytosine DNA immunoprecipitation (hMeDIP) sequencing. Expression of mRNA and proteins was detected by qRT-PCR and western blot respectively. The proliferation and migration of VSMCs were assessed by EdU assay, flowcytometry assay, and wound healing assay. LEMD2 overexpression and knockdown stable VSMC lines were established through Lentiviral infection. Results: The EdU assay and wound healing assay show that knockdown of TET2 enhanced proliferation and migration of VSMCs. NGS identified 123 differentially expressed genes (91 up-regulated and 32 down-regulated) between TET2 knockdown VSMCs and control VSMCs while hMeDIP sequencing identified 166 genes with differentially hydroxymethylated promoter region (68 up-regulated and 98 down-regulated) between TET2 knockdown VSMCs and control VSMCs. Through comparing these sequencing results, we identified a gene named as LEMD2 simultaneously present in both sequencing results. Expression of LEMD2 at mRNA and protein level was significantly increased in TET2 knockdown VSMCs compared to control VSMCs. Then we successfully established LEMD2 overexpression and knockdown stable VSMC lines and found that overexpression of LEMD2 enhanced proliferation and migration of VSMCs while knockdown of LEMD2 inhibited proliferation and migration of VSMCs. Furthermore, overexpression of LEMD2 up-regulated the expression of NOX1 and down-regulated the expression of NOX4 while knockdown of LEMD2 show the opposite effect. Conclusion: The present study confirmed that TET2 modulates VSMC proliferation and migration via LEMD2/NOX1/NOX4. The ROS level may be involved in VSMC proliferation and migration. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National natural science foundation of China